CTLA4 +49AG (rs231775) and CT60 (rs3087243) gene variants are not associated with alopecia areata in a Mexican population from Monterrey Mexico - Salinas Santander, Mauricio Andrés; Cantú Salinas, Cristina Susana; Ocampo Candiani, Jorge; Suarez Valencia, Victor de Jesus; Ramirez Guerrero, Jennifer Guadalupe; Sánchez Domínguez, Celia Nohemí (2020)
Background: Alopecia areata is an autoimmune disease that produces non-scarring hair loss around the body. Gene variants of the cytotoxic T-lymphocyte antigen 4 (CTLA4) gene, a negative regulator of T-cell response, have been associated with a predisposition to autoimmune diseases in different populations; however, the involvement of these genetic variants in the development of AA is controversial. Objective: The present study evaluated the potential association of two CTLA4 gene variants with alopecia areata in a Mexican population. Methods: We genotyped +49AG (rs231775) and CT60 (rs3087243) variants in 50 AA patients and 100 healthy control participants through PCR-RFLP. Results: No statistical difference was observed for either of the gene variants regarding allele or genotype frequencies between AA patients and the controls when the parameters of family/personal history of autoimmune diseases or gender were considered (p > 0.05).Study limitations: Small sample size of patients and the data were obtained from NortheastMexico population.Conclusion: The genetic variants rs231775 and rs3087243 of the CTLA4 gene are not a risk factorfor the development of alopecia areata in the analyzed Mexican population